Improving acid resistance of Escherichia coli base on the CfaS-mediated membrane engineering strategy derived from extreme acidophile - Hu, Wenbo; Tong, Yanjun; Liu, Junjie; Chen, Panyan; Yang, Hailin; Feng, Shoushuai (Frontiers in Bioengineering and Biotechnology, 2023)
Industrial microorganisms used for the production of organic acids often face challenges such as inhibited cell growth and reduced production efficiency due to the accumulation of acidic metabolites. Therefore, how to improve the acid resistance of microbial cells is a key issue that has been repeatedly discussed. In this study, Overexpressing the cfa2 from extreme acidophile improved the resistance of E. coli to moderate acid stress. Subsequently, the engineered strain M1-93-Accfa2, constructed by integrating Accfa2 into the E. coli genome using the CRISPR-Cas9 dual-plasmid system, presented a significantly increased resistance to severe acid stress (pH 4.8). The analysis of fatty acid profiles showed that the proportions of two cyclopropane fatty acids (CFAs), Cy-17:0 and Cy-19:0, in the cell membrane of M1-93-Accfa2 increased by 1.26 and 5.26 times, respectively. Meanwhile, two unsaturated fatty acids (UFAs), C16:1w9c and C18:1w9c, decreased by 1.31 and 5.81 times, respectively, compared with the control strain. Correspondingly, its membrane permeability and fluidity were significantly reduced. HPLC analysis demonstrated that the contents of several free amino acids closely related to acid resistance in M1-93-Accfa2 cells after environmental acidification, such as glutamic acid, arginine, methionine and aspartic acid, were 2.59, 2.04, 22.07 and 2.65 times that of the control strain, respectively. Meanwhile, TEM observation indicated that M1-93-Accfa2 could maintain a plumper cell morphology after acid stimulation than other strains. M1-93-Accfa2 also exhibited excellent resistance to organic acids, especially succinic acid stress. Overall, the engineering strain M1-93-Accfa2 constructed in this study exhibited excellent performance in the resistance to acid stress and had potential application value in organic acid production.